THE INFLUENCE OF PROFITABILITY ON FIRM VALUE IN COSUMER NON-CYCLICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2022–2024 PERIOD - NUGRAHINI, JESSENIA NADHITA; RAMADHANI, ALYA AYU SUCI; NURHAINI, NABILA KURNIA (Kampus 5 Universitas Negeri Surabaya, 2025)
This study investigates the influence of profitability on firm value in companies operating in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Profitability, represented by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), serves as the independent variables, while firm value is proxied by Price to Book Value (PBV). The research aims to determine whether profitability ratios significantly affect firm value, either partially or simultaneously. The study employs a quantitative approach using secondary data obtained from annual financial statements published by the IDX. The analytical method used is multiple linear regression, supported by classical assumption tests to ensure data validity and reliability. The findings indicate that profitability has a positive and significant effect on firm value, suggesting that higher profitability enhances investor confidence and increases the market valuation of the firm. Among the profitability indicators, ROE shows the strongest influence on PBV, highlighting shareholders’ efficiency as a key driver of firm value. These results provide empirical evidence supporting the relevance of profitability as a determinant of firm valuation and offer managerial implications for improving financial performance to strengthen firm market position. Keywords: Profitability, Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Firm Value, Price to Book Value (PBV)